A Comparison of Dental Caries in Urban and Rural Children of the Riyadh Region of Saudi Arabia - Al-Rafee, Mohammed A.; AlShammery, Abdullah R.; AlRumikan, Ali S.; Pani, Sharat C. (Frontiers in Public Health, 2019)
Background and Aim: The data presented in this study aims aimed to document the overall caries prevalence rate and severity among a representative sample of 6, 12 and 15 year old Saudi Children. Methodology: The data in this study was collected as part of a regional pathfinder study. 1986 school children from 75 schools in urban and rural areas of Riyadh region, Saudi Arabia. Children having one or more dental caries lesion were used to determine prevalence of dental caries. Total number of decayed filled teeth (dft) was used to assess caries severity at in the 6year group while the DMFT was used to assess severity of dental caries at the 12years and 15 years age group. Results: The caries prevalence was 85.77% at 6yearsin the 6 year group, 85.43% at in the 12 year group s and 71.35% at in the 15 year groups. Mean dft was 1.4 (SD+/-1.1). The mean DMFT was 1.72(SD+/- 0.49) at 12 years and 2.66 (SD+/- 0.55) at 15years. Both caries rate and severity were higher in rural areas than urban areas although the differences were not statistically significant. Conclusion: The results of this study suggest minor decrease in caries rates in Saudi Arabia when compared to the previous nationwide calibrated data. However, both caries prevalence and caries severity are still higher than global averages Keywords: Dental Caries, Dental Public Health, Oral Health Surveys